A cytotoxic leachable compound from single‐use bioprocess equipment that causes poor cell growth performance. (5th February 2014) - Hammond, Matthew; Marghitoiu, Liliana; Lee, Hans; Perez, Lourdes; Rogers, Gary; Nashed‐Samuel, Yasser; Nunn, Heather; Kline, Sally
<x xml:space="preserve">Abstract</x> A current trend in the production of biopharmaceuticals is the replacement of fixed stainless steel fluid‐handling units with disposable plastic bags. Such single‐use systems (SUS) offer numerous advantages, but also introduce a new set of materials into the production process and consequently expose biomanufacturers to a new set of risks related to those materials, not to mention reliance on an entirely new supply chain. In the course of developing and conducting a cell‐growth‐based test for suitability of disposable plastic components destined for use in cell culture operations, we discovered that the cytotoxic compound bis(2, 4‐di‐tert‐butylphenyl)phosphate (bDtBPP) leaches out of certain bags and into cell culture media in concentrations that are deleterious to cell growth. Specifically, media held in certain bags for several days at 37°C was found to contain bDtBPP, and use of those held‐media samples in cell growth experiments provides data that overlap neatly with cell growth experiments using media spiked directly with bDtBPP, proving that bDtBPP leaching is responsible for the reduced growth attributable to those SUS bags. Overall, this issue represents a risk to the production of biopharmaceuticals in SUS, a risk that must be managed by diligent collaboration among companies along the entire supply chain for SUS components. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:332–337, 2014